Hyperthermia and radiotherapy in the management of head and neck cancers: A systematic review and meta-analysis. (2nd January 2016) - Datta, Niloy R.; Rogers, Susanne; Ordóñez, Silvia Gómez; Puric, Emsad; Bodis, Stephan
Abstract: Purpose : A systematic review and meta-analysis was conducted to evaluate the outcome of controlled clinical trials in head and neck cancers (HNCs) using hyperthermia and radiotherapy versus radiotherapy alone. Material and methods : A total of 498 abstracts were screened from four databases and hand searched as per the PRISMA guidelines. Only two-arm studies treating HNCs with either radiotherapy alone, or hyperthermia and radiotherapy without concurrent chemotherapy or surgery were considered. The evaluated end point was complete response (CR). Results : Following a detailed screening of the titles, abstracts and full text papers, six articles fulfilling the above eligibility criteria were considered. In total 451 clinical cases from six studies were included in the meta-analysis. Five of six trials were randomised. The overall CR with radiotherapy alone was 39.6% (92/232) and varied between 31.3% and 46.9% across the six trials. With thermoradiotherapy, the overall CR reported was 62.5% (137/219), (range 33.9–83.3%). The odds ratio was 2.92 (95% CI: 1.58–5.42, p  = 0.001); the risk ratio was 1.61 (95% CI: 1.32–1.97, p  < 0.0001) and the risk difference was 0.25 (95% CI: 0.12–0.39, p  < 0.0001), all in favour of combined treatment with hyperthermia and radiotherapy over radiotherapy alone. Acute and late grade III/IV toxicities were reported to be similar in both the groups. Conclusions : Hyperthermia along with radiotherapy enhances the likelihood of CR in HNCs by around 25% compared to radiotherapy alone with no significant additional acute and late morbidities. This level I evidence should justify the integration of hyperthermia into the multimodality therapy of HNCs.